The Politics of the Société Saint-Jean-Baptiste de Montréal - Agen, Marie-Catherine (American Review of Canadian Studies, 1999)
issued: 1999-23-00
Keywords: Francophones; Nationalisme; Société Saint-Jean-Baptiste

Le mouvement ouvrier juif au Canada (1904-1920) - Belkin, Simon (Septentrion, 1999)
Keywords: Congrès juif canadien; Juifs; Poalei Zion (Mouvement sioniste ouvrier)

Parcours d'un marqueur sociolinguistique: les pronoms non-clitiques du pluriel en français parlé de Montréal - Blondeau, Hélène (Université de Montréal, 1999)
Keywords: Langue

L'unilinguisme français et le projet souverainiste du Parti québécois vus par la communauté juive du Québec (1974-1981) - Cloutier, Caroline (Bulletin d'histoire politique, 1999)
issued: 1999-23-00
Keywords: Juifs; Langue; Nationalisme; Partis politiques

Understanding the Patterns of Language Use of Chinese Children in a Montreal Community School - Curdt-Christiansen, Xiao Lan (Université McGill, 1999)
Keywords: Chinois; Langue; Étudiants

La colocation comme situation de communication interculturelle, le discours de cinq jeunes français vivant avec des québécois - Ferrand, Nathalie (Université du Québec à Montréal, 1999)
Keywords: Français; Locataires; Logement

"Des Québécois importés et leurs niches": l'immigration et l'expression de l'ethnicité dans les pratiques économiques des Portugais indépendants du Québec - Fonséca, Félix (Université Laval, 1999)
Keywords: Portugais

Réflexions sur les pratiques communicationnelles des institutions de la société d'accueil dans l'insertion des immigrantes et des immigrants au Québec: 1986-1996 - Fournel, Claude-Jean (Université du Québec à Montréal, 1999)

Exile, Transnational Connections, and the Construction of Identity: Tibetan Immigrants in Montreal - Gardner, Jane (Université Concordia, 1999)
Keywords: Tibétains

Les quartiers multiethniques montréalais: une lecture urbaine - Germain, Annick (Recherches sociographiques, 1999)
Number: 1
Keywords: Quartiers

English Caribbean Immigrant Entrepreneurs in Montreal - Hall, Margaret-Ann (Université Concordia, 1999)
Keywords: Anglophones; Caribéens

Writing Bodies: Modern Dance, Gender, and Jewish Identity in New York and Montreal, 1930 to 1960 - Hardt, Yvonne (Université Concordia, 1999)
Keywords: Danse; Juifs

Les immigrants préférés: Les Belges - Jaumain, Serge (Presses de l'Université d'Ottawa, 1999)
Keywords: Belges

L'immigration belge au Canada: une histoire en devenir - Jaumain, Serge; Sanfilippo, Matteo (Les immigrants préférés: Les Belges, 1999)
Keywords: Belges

L'expérience vécue par des jeunes maghrébins dans des centres de réadaptation à Montréal - Jouiet, Rabina (Université de Montréal, 1999)
Keywords: Maghrébins

L'identité transnationale et l'installation des Chinois du Vietnâm à Montréal - LaRochelle, Jean (Université de Montréal, 1999)
Keywords: Chinois

Expulsion des immigrants indésirables à Montréal: 1911-1914 - Legeay, Guilaine (Université d'Angers, 1999)

Community and Identity in Nineteenth Century Montreal: The Founding of Saint Patrick's Church - Leitch, Gillian I. (Université d'Ottawa, 1999)
Keywords: Irlandais; St. Patrick (église); Églises

Montreal's Scottish Community, 1835-65: A Preliminary Study - McNabb, Heather (Université Concordia, 1999)
Keywords: Écossais

Des Italo-Belges au Canada: résultats d'une première enquête - Morelli, Anne (Les immigrants préférés: Les Belges, 1999)
Keywords: Belges; Italiens

Entente cordiale? La section montréalaise du Fonds patriotique canadien, 1914-1923: le bénévolat de guerre à Montréal - Morton, Desmond (Revue d'histoire de l'Amérique française, 1999)
issued: 1999-23-00
Keywords: Bénévolat; Guerre

Les relations interculturelles entre les immigrants d'origine sénégalaise et la population d'accueil québécoise: jalons d'une analyse des systèmes de représentation et des stratégies d'intégration - Ndoye, Amadou (Université Laval, 1999)
Keywords: Sénégalais

La transmission d'une mémoire sociale à travers quatre générations: le cas des Juifs ashkénazes à Montréal - Olazabal, J.-Ignace (Université de Montréal, 1999)
Keywords: Juifs

Education and Integration of Immigrant Minorities: A Case Study of the Haitian Community in Quebec - Pompilus, Léopold (Université Concordia, 1999)
Keywords: Haïtiens

Becoming Native in a Foreign Land: Visual Culture, Sport, and Spectacle in the Construction of National Identity in Montreal, 1840-1885 - Poulter, Gillian (York University, 1999)
Keywords: Autochtones; Britanniques; Français

Motivation in Hip-Hop Graffiti Culture: The Site of Tension between Individual Desire, Peer Influence and Community Space - Rahn, Janice (Université Concordia, 1999)

The Kahnawake Iroquois and the Lower-Canadian Rebellions, 1837-1838 - Sossoyan, Matthieu (Université McGill, 1999)
Keywords: Autochtones; Iroquois; Rébellions

La famille juive à Montréal au tournant du XXe siècle - Soucy, Isabelle (Université du Québec à Montréal, 1999)
Keywords: Famille; Juifs

The Jackie Robinson Myth: Social Mobility and Race in Montreal, 1920-1960 - Williams, Dorothy W. (Université Concordia, 1999)
Keywords: Enseignants; Lord; Gwen; Lord; Richard; Noirs; Robinson; Jackie

Ethnicity and Home Ownership in Montreal, 1921–51 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1998)
Number: 2
Keywords: Locataires; Logement

Une quête identitaire entre mythe et histoire: les Juifs ashkénazes à l'aventure de l'Amérique en Québec - Barriault, Lise (Université du Québec à Montréal, 1998)
Keywords: Juifs

Quelques observations sur les mariages irlandais dans la paroisse Notre-Dame de Montréal (1840-1861) - Beaudoin, Philippe (Canadian Ethnic Studies / Études ethniques au Canada, 1998)
Number: 1
Keywords: Irlandais; Mariage; Notre-Dame (paroisse)

Le travail d'établissement des réfugiés salvadoriens à Montréal - Beausoleil, Julie (Université de Montréal, 1998)
Keywords: Salvadoriens

Les radios communautaires et leurs publics CIBL face à l'indifférence de l'auditoire d'origine africaine - Belibi Mengueme, Mireille Simone (Université du Québec à Montréal, 1998)
Keywords: Africains; Radio

Pour un patrimoine pluriethnique - Blanc, Bernadette (Continuité, 1998)
issued: 1998-21-00
Keywords: Côte-des-Neiges; Patrimoine; Quartiers

Étude descriptive du phénomène d'intégration de la communauté libanaise à la société québécoise à Montréal - Chamoun, Myrna (Université du Québec à Montréal, 1998)
Keywords: Libanais

Shadrach Minkins: From Fugitive Slave to Citizen - Collison, Gary (Harvard University Press, 1998)
Keywords: Esclaves; Noirs

Influence du processus d'insertion sur l'identité des femmes libanaises nouvellement arrivées à Montréal - Cossette, Maryse (Université du Québec à Montréal, 1998)
Keywords: Femmes; Libanais

Les descendants d'Hochelaga: étude de la représentation autochtone à travers le toponyme Hochelaga et les productions artistiques et commerciales du Vieux-Montréal - Doiron, Roger (Université du Québec à Montréal, 1998)
Keywords: Autochtones; Quartiers; Vieux-Montréal

Bagarres entre militaires et "zoot-suiters" survenues à Montréal et à Verdun en juin 1944: problème de langue, de relations entre civils et militraires ou de rébellion juvénile? - Durflinger, Serge Marc (L'impact de la Deuxième Guerre mondiale sur les sociétés canadienne et québécoise, 1998)
Keywords: Armée; Vêtements

Adaptation post-migratoire des couples marocains à Montréal: satisfaction maritale et stress psychologique - El Haïli, Saïda (Université de Montréal, 1998)
Keywords: Maghrébins; Marocains

Les organisations féminines de la communauté juive montréalaise, 1918-1948 - Filotas, Sarah (Université de Montréal, 1998)
Keywords: Femmes; Juifs

An Age Rich in Miracles - Fournier, Marcel; Rodriguez, Véronique (Montreal Metropolis, 1880-1930, 1998)

Une époque fertile en miracles - Fournier, Marcel; Rodriguez, Véronique (Montréal métropole, 1880-1930, 1998)

An Exploratory Study of a Group of Montréal Anglophone Teachers' Attitudes toward Multicultural Education - Ganji, Mahnaz (Université du Québec à Montréal, 1998)
Keywords: Anglophones; Enseignants

Les quartiers multiethniques montréalais, lieux de sociabilité publique - Germain, Annick (Barcelona-Montréal: desarrollo urbano comparado / développement urbain comparé, 1998)
Keywords: Quartiers

Différenciation sociale et rituels du mariage: les Montréalais francophones, 1925-1940 - Girard, Denise (Université Laval, 1998)
Keywords: Francophones; Mariage

Genèse d'une communauté lesbienne: un récit des années 1970 - Hildebran, Andrea (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Anglophones; Femmes; Francophones

Gender, Race, and Power: the Chinese in Canada, 1920-1950 - Huang, Belinda (Université McGill, 1998)
Keywords: Chinois

Die Geschichte des deutschsprachigen Theaters in Montreal von seinen Anfängen 1953 bis 1997 - Kremer, Johanna (Université McGill, 1998)
Keywords: Allemands; Théâtre

La mise en place des paysages ethniques, 1871-1971 - McNicoll, Claire (Montréal 2001. Visages et défis d'une métropole, 1998)

L'intervention de réadaptation auprès des adolescents haïtiens: problèmes rencontrés, compréhension du phénomène et pistes d'intervention - Mercier, Chantale (Université du Québec à Trois-Rivières, 1998)
Keywords: Haïtiens

Renegotiating Home and Identity: Experiences of Gujarati Immigrant Women in Suburban Montreal - Nair, Roopa (Université McGill, 1998)
Keywords: Femmes; Indiens

Fascism and the Italians of Montreal: an Oral History, 1922-1945 - Salvatore, Filippo (Guernica, 1998)
Translators: _:n17371
Keywords: Idéologies; Italiens

Le processus identitaire dans le soccer chez les italiens de Montréal - Spadari, Luigi (Université de Montréal, 1998)
Keywords: Italiens; Soccer

L'identité des immigrants latino-américains à Montréal - Thomas, Ève (Université de Montréal, 1998)
Keywords: Latino-Américains

Le phénomène des jeunes de la rue à Montréal le cas des Haïtiens - Uwumuremyi, Marie D'Amour (Université du Québec à Montréal, 1998)
Keywords: Haïtiens; Itinérance

The Senator, The Merchant, Two Carpenters and a Widow: A Survey of Canadian Landlords in 1871 - Burley, David G. (Urban History Review / Revue d'histoire urbaine, 1997)
Number: 2
Keywords: Logement

Imagining Ethnicity. The Role of the Montreal Bangladeshi Press in Ethnic Cohesion - Ahmed, Shameem (Université McGill, 1997)
Keywords: Bengalis

Arab Immigrants in the Canadian Labour Market Expectations and Compromises - Al-Hihi, Mahmoud M (Université Concordia, 1997)
Keywords: Arabes; Travail

Tur Malka: flâneries sur les cimes de l'histoire juive montréalaise - Anctil, Pierre (Septentrion, 1997)
Keywords: Juifs

Les scénarios sexuels des jeunes adultes latino-américains de Montréal l'impact de l'acculturation et du genre - Arroyo, Javiera (Université du Québec à Montréal, 1997)
Keywords: Latino-Américains

Cloisonnement ethnique et solidarité captive. Famille Lao dans le quartier Côte-des-Neiges - Bertheleu, Hélène; Billion, Pierre (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Laotiens; Quartiers

Vivre un choc culturel à 65 ans: le cas des personnes âgées haïtiennes en HLM à Montréal - Bontemps, Eva (Université du Québec à Montréal, 1997)
Keywords: Haïtiens; Logement

Tendances de l’assimilation linguistique dans l'ouest de l’île de Montréal et l’ouest de l’Outaouais de 1971 à 1991 - Castonguay, Charles (Cahiers québécois de démographie, 1997)
issued: 1997-23-00
Keywords: Anglophones; Francophones; Langue

Étude de l'appartenance au groupe "Québécois" à partir des images et des identités véhiculées par la presse communautaire à Montréal - Contandriopoulos, Damien (Université de Montréal, 1997)
Keywords: Journalistes

Montréal, les Juifs et l'école - Corcos, Arlette (Septentrion, 1997)
Keywords: Juifs

La construction médiatique du "Bronx" de Montréal - El Yamani, Myriame; Dupuis, Jocelyne (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Les Libanais d'immigration récente: insertion ou exclusion? - Fortin, Sylvie (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Libanais; Quartiers

Utilisation des caractéristiques dialectales du français québécois par un groupe d'anglophones bilingues de Montréal - Frigon, Chantal (Université de Montréal, 1997)
Keywords: Langue

Pour en finir avec un mythe: le refus des écoles catholiques d'accepter les immigrants - Gagnon, Robert (Bulletin d'histoire politique, 1997)
issued: 1997-24-00
Keywords: Commission des écoles catholiques de Montréal

La signification des soins reliés à la grossesse et à l'accouchement de couples iraniens à Montréal - Gharehbagh, Zahra A. (Université de Montréal, 1997)
Keywords: Iraniens

Les organisations de solidarité avec le Chili à Montréal, 1973-1993 - Hervas Segovia, Epiganio Roberto (Université du Québec à Montréal, 1997)
Keywords: Chiliens

The Saint Patrick's Society of Montreal: Ethno-Religious Realignment in a Nineteenth-Century National Society - James, Kevin (Université McGill, 1997)
Keywords: Irlandais

Jackie Robinson: une inoubliable saison de baseball à Montréal - Jedwab, Jack (Les Éditions Images, 1997)
Keywords: Baseball; Robinson; Jackie

L'entrepreneurship à Côte-des-Neiges: le périmètre Victoria / Van Horne - Juteau, Danielle; Paré, Sylvie (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

La perception de la qualité de la langue au Québec de 1960 à 1992 d'après les opinions publiées dans La Presse - Lajeunesse, Lyse (Université de Sherbrooke, 1997)
Keywords: Langue; Presse (La)

Ethnic Political Participation in Montreal: the Role of Community Leaders - Lapp, Miriam (Université de Montréal, 1997)
Keywords: Chinois; Grecs; Italiens; Juifs; Portugais; Élections

Espaces observés: ethnicité et appropriation territoriale - Le Gall, Josiane; Meintel, Deirdre (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

La reconquête de Montréal - Levine, Marc V. (VLB Éditeur, 1997)
Keywords: Anglophones; Francophones

Destination: Montréal: l'étude de l'émigration en provenance de Casacalenda (Molise, Italie) - Malpas, Nicole (Cahiers québécois de démographie, 1997)
issued: 1997-23-00
Keywords: Italiens

Le Montréal juif d'autrefois / Monṭreol fun nekhṭen - Medresh, Israël (Septentrion, 1997)
Translators: _:n16920
Keywords: Juifs

Étudier la pluriethnicité à l'ère de la mondialisation - Meintel, Deirdre; Piché, Victor; Fortin, Sylvie (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité - Meintel, Deirdre; Piché, Victor; Juteau, Danielle; Fortin, Sylvie (L'Harmattan, 1997)
Keywords: Côte-des-Neiges; Quartiers

Nature et corrélats des orientations d'acculturation chez des Antillais à Montréal - Moïse, Léna Céline (Université du Québec à Montréal, 1997)
Keywords: Caribéens

Étude exploratoire sur l'adaptation socio-sexuelle des immigrants latino-américains gais à Montréal - Pérez Luis, Javier Éric (Université du Québec à Montréal, 1997)
Keywords: Latino-Américains

L'insegnamento dell'italiano a Montreal verso il Duemila. Insegnamento e apprendimento al livello post-secondario in un contesto plurilingue - Picciano, Giovanna A. (Université McGill, 1997)
Keywords: Italiens; Langue

Le quartier Côte-des-Neiges: fiction statistique ou milieu d'insertion pour les groupes d'immigrants? - Piché, Victor; Bélanger, Liane (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1997)
Keywords: Côte-des-Neiges; Quartiers

Les jeunes de la deuxième génération haïtienne au Québec: entre la communauté « réelle » et la communauté « représentée » - Potvin, Maryse (Sociologie et sociétés, 1997)
issued: 1997-23-00
Keywords: Haïtiens

Histoire et histoires dans la métropole québécoise: le quartier Côte-des-Neiges - Ramirez, Bruno (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Les Franco-Américains à Montréal au début du XXe siècle - Rodrigue, Martine (Université du Québec à Montréal, 1997)
Keywords: Américains; Francophones

L'immigré salvadorien à Montréal: interprétation d'un processus d'intégration - Ruano, Mauricio (Université du Québec à Montréal, 1997)
Keywords: Salvadoriens

Rapports sociaux-ethniques à Côte-des-Neiges, un quartier de Montréal - Simon-Barouh, Ida (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Irish Radicalism and the Roman Catholic Church in Quebec and Ireland, 1833-1834: O'Callaghan and O'Connell Compared - Slattery, Maureen (Canadian Catholic Historical Association, Historical Studies, 1997)
Keywords: Irlandais; O'Callaghan; Edmund B.; Rébellions; Églises

Le contrôle social et la construction de l'Autre: la police dans un quartier multiethnique - Symons, Gladys L.; Loiselle, Marie-Josée (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Police; Quartiers

Minorités, majorités et les territoires du quotidien - Ulysse, Pierre Joseph; McAll, Christopher (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Représentations sociales de la culture des jeunes de la communauté haïtienne de Montréal et construction de leur identité - Valéry, Joseph Olivier (Université de Montréal, 1997)
Keywords: Haïtiens

The Road to Now: A History of Blacks in Montreal - Williams, Dorothy W. (Véhicule Press, 1997)
Keywords: Noirs

Romanticism, Home, and Death: Elements in the Lives of the Anglophone Elite in Early Victorian Montreal - Young, Brian (Australian-Canadian Studies, 1997)
Number: 1
Keywords: Anglophones

Politiques d'intégration et résistances ethniques au Québec: le cas d'immigrants libanais depuis 1975 - Abou-Hsab, Gaby (Université du Québec à Montréal, 1996)
Keywords: Libanais

La situation sociolinguistique de la communauté marocaine musulmane de Montréal - Boukkouri, Mohammed (Université du Québec à Montréal, 1996)
Keywords: Maghrébins; Marocains; Musulmans

Identité ethnique et acculturation chez des étudiants juifs sépharades à Montréal - Brami, Paula (Université de Montréal, 1996)
Keywords: Juifs; Étudiants

Antiracism organizing and resistance in nursing : African Canadian Women - Calliste, Agnes (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1996)
Number: 3
Keywords: Africains; Femmes; Infirmières; Noirs

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

Les étrangers sous le Régime français - Grenier, Hélène (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)

Locating Crisis Representations of Race and Space in the English media, Montreal, 1987-1992 - Hadlaw, Janin (Université Concordia, 1996)
Keywords: Montreal Gazette; Noirs; Police; Télévision

Analyse fonctionnelle et sociolinguistique de la particule discursive OK en français montréalais - Heisler, Troy (Université Laval, 1996)
Keywords: Francophones

Notre maître: le passé? Nationalisme et antisémitisme au Devoir, 1932-1947 - Jedwab, Jack (Le Devoir: un journal indépendant, 1910-1995, 1996)
Keywords: Devoir (Le); Juifs; Nationalisme

Adaptation and Integration Process of some African Ismaili Youths of Second-Generation in Montreal - Jinah, Parvin (Université de Montréal, 1996)
Keywords: Africains

Les esclaves aux 17e et 18e siècles - Lachance, André (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)
Keywords: Autochtones; Esclaves; Noirs

Les Amérindiens sous le Régime français - Lachance, André; Savoie, Sylvie (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)
Keywords: Autochtones

Le théâtre yiddish à Montréal / Yiddish Theatre in Montreal - Larrue, Jean-Marc (Jeu, 1996)
Keywords: Juifs; Théâtre

Les facteurs de maintien de l'identité collective arménienne chez les jeunes adultes de la diaspora montréalaise - Lenoir-Achdjian, Annick (Université de Montréal, 1996)
Keywords: Arméniens

Interkulturelle Landeskunde im Bereich des Deutschen als Fremdsprache an kanadischen Hochschulen: Dokumentation einer Fallstudie am Department of German Studies der McGill University, Montreal, Quebec, Kanada - Mollinger, Karin (Université McGill, 1996)
Keywords: Allemands; Université McGill

Identity, Place and Community: A Latin American Locale in Montreal - Occhipinti, Joseph (Université McGill, 1996)
Keywords: Latino-Américains

Le peuplement de Montréal - Olson, Sherry (Atlas historique du Québec. Population et territoire, 1996)

Trabajo Asalariado, género e identidad: la inserción de las Mujeres Colombianas en Montreal - Osorio Ramírez, Amantina Maria (Université de Montréal, 1996)
Keywords: Colombiens; Femmes; Travail

Influence de l'acculturation sur l'alimentation des haïtiennes de Montréal - Petit, Éva (Université de Montréal, 1996)
Keywords: Alimentation; Haïtiens

Representing Twentieth Century Canadian colonial Identity: the Imperial Order Daughters of the Empire (IODE) - Pickles, Catherine Gillian (Université McGill, 1996)
Keywords: Britanniques; Femmes

Le dictionnaire de bon langage d'Étienne Blanchard: étude métalexicographique; contribution à l'histoire de la lexicographie québécoise - Prévost, Geneviève (Université Laval, 1996)
Keywords: Linguistique

Strategies of Survival Among Illegal Migrants in Montreal - Raposo, Cremilde (Université Concordia, 1996)
Keywords: Travail

A Foothold in the Whirlpool: Canada's Iberian Refugee Movement - Reed, Patrick (Université Concordia, 1996)
Keywords: Juifs

Les représentations d'adolescents d'origine haïtienne (14 ans et plus) de la région de Montréal de leur intégration sociale à l'école secondaire et de leur identité culturelle - Valcin, Paul-Bermude (Université du Québec à Montréal, 1996)
Keywords: Haïtiens

Essai de définition: les sculpteurs, statuaires et ornemanistes italiens à Montréal: de 1862 à 1880 - Vignola, Luce (Université du Québec à Montréal, 1996)
Keywords: Artisans; Italiens; Sculpture

Les communautés protestantes francophones au Québec, 1834-1925 - Vogt-Raguy, Dominique (Université Michel de Montaigne-Bordeaux 3, 1996)
Keywords: Francophones; Protestants

City Unique: Montreal days and nights in the 1940s and '50s - Weintraub, William (McClelland & Stewart, 1996)

Cultures en fragments: l'ethnicité et la religion chez les migrants indo-trinidadiens de Montréal - Beauchemin, Robert (Université de Montréal, 1995)
Keywords: Indiens

L'idée du refus comme mémoire et comme identité chez les artisans visuels contemporains québécois - Carani, Marie (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)
Keywords: Borduas; Paul-Émile; Peinture

Élites et organisation communautaire chez les juifs marocains à Montréal - Cohen, Yolande; Lévy, Joseph (Annuaire de l'Émigration, 1995)
Keywords: Juifs; Maghrébins; Marocains

Moroccan Jews and their Adaptation to Montreal Life - Cohen, Yolande; Lévy, Joseph J. (Renewing our Days: Montreal Jews in the Twentieth Century, 1995)
Keywords: Juifs; Maghrébins; Marocains

La réception critique de la peinture de Jean Paul Lemieux ou la construction d'une figure identitaire - Couture, Francine (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)
Keywords: Peinture

Les immigrants français à Montréal, 1850-1901. Étude des Français présents à Montréal lors du recensement de 1901 - Filot, Ingrid (Université Lumière Lyon 2, 1995)
Keywords: Français

Borduas revu à travers la figure de Claude Gauvreau - Fisette, Jean (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)
Keywords: Automatistes; Borduas; Paul-Émile

Les Libanais d'immigration récente à Montréal: insertion ou exclusion - Fortin, Sylvie (Université de Montréal, 1995)
Keywords: Libanais

Les immigrants hispanophones de Montréal et leurs attitudes par rapport aux deux langues officielles - Franco, Barbara (Université du Québec à Montréal, 1995)
Keywords: Espagnols; Langue

La solidarité entre générations: Haïtiennes âgées à Montréal - Haldemann, Varena (Sociologie et sociétés, 1995)
issued: 1995-23-00
Keywords: Femmes; Haïtiens

La peur de l'étranger: les Chinois à Montréal de 1885 à 1947 - Harel, Nathalie (Université de Montréal, 1995)
Keywords: Chinois

A Study of the Effects of Acculturation on Sex-Role Attitudes of Chinese Couples, and the Subsequent Impact of these Sex-Role Attitudes on Couple's Household Task Sharing & Decision Making - Hayes, Janet (Université Concordia, 1995)
Keywords: Chinois; Femmes

Emparons-nous du sport: les Canadiens français et le sport au XIXe siècle - Janson, Gilles (Guérin, 1995)
Keywords: Francophones

Presse ethnique et socialisation politique: le cas de la communauté chinoise de Montréal - Jolicœur, Martin (Université Laval, 1995)
Keywords: Chinois

Collaboration inter-organisationnelle dans un contexte ethnique à Montréal - Kimonyo, Jean-Paul (Université de Montréal, 1995)

Blacks in Québec Society, Past and Present - La Grenade-Meunier, Monique; Fehmiu Brown, Paul (Ministère des Affaires internationales, de l'Immigration et des Communautés culturelles et ministère de l'Éducation, 1995)
Keywords: Noirs

La présence des Noirs dans la société québécoise d'hier et d'aujourd'hui - La Grenade-Meunier, Monique; Fehmiu Brown, Paul (Ministère des Affaires internationales, de l'Immigration et des Communautés culturelles et ministère de l'Éducation, 1995)
Keywords: Noirs

Les visages du Plateau Mont-Royal - LaFerrière, Suzanne (Continuité, 1995)
issued: 1995-23-00
Keywords: Plateau Mont-Royal; Quartiers

L’ethnicisation de l’établissement humain en Amérique du Nord: l’exemple du quartier portugais à Montréal - Lavigne, Gilles; Daudelin, Nanouk; Ritchot, Gilles (Cahiers de géographie du Québec, 1995)
Number: 108
Keywords: Portugais; Quartiers

Représentation et rôle des Québécois / Canadiens français dans le radioroman de guerre 1939-1945 - Legris, Renée (Bulletin d'histoire politique, 1995)
issued: 1995-21-00/1995-22-00
Keywords: Guerre; Radio; Roman

Chinese-Canadian Women in Montreal: Case Studies in the Importance of Education - Li, Sharon (Université McGill, 1995)
Keywords: Chinois; Femmes

Le monde du travail comme moyen d'intégration des Portugais au Québec (1953-1995): ou comment marier le vieux et le neuf - Lopes, Duarte (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1995)
issued: 1995-22-00
Keywords: Portugais

La polysensorialité dans les discours symboliques plastiques québécois (1930-1960) - Lupien, Jocelyne (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)

La concentration ethnique dans les écoles de langue française de l’île de Montréal: un portrait statistique - Mc Andrew, Mary; Ledoux, Michel (Cahiers québécois de démographie, 1995)
issued: 1995-23-00
Keywords: Francophones; Langue

The Indian Business Community in Montreal from 1967 to 1991 - Meenakshi, Gupta (Université du Québec à Trois-Rivières, 1995)
Keywords: Hommes d'affaires; Indiens

Le raz de marée irlandais à Montréal - Olson, Sherry; Thornton, Patricia (Les chemins de la migration en Belgique et au Québec: XVIIe-XXe siècles, 1995)
Keywords: Irlandais

Canadiens français et non-francophones dans les villes québécoises et ontariennes, 1851-1911: une perspective comparative et régionale - Ouellet, Fernand (La francophonie ontarienne: bilan et perspectives de recherche, 1995)
Keywords: Francophones

Chronique d'une Académie, 1944-1994: de l'Académie canadienne-française à l'Académie des lettres du Québec - Royer, Jean (L'Hexagone, 1995)
Keywords: Linguistique

Le fascisme et les Italiens à Montréal: une histoire orale, 1922-1945 - Salvatore, Filippo (Guernica, 1995)
Keywords: Idéologies; Italiens

Usages familiaux des médias en situation de transition: le cas de sept Roumains à Montréal - Theodorescu, Christiana-Nicola (Université du Québec à Montréal, 1995)
Keywords: Roumains

Les paramètres épistémologiques et idéologiques d'un premier discours sur la modernité - Trépanier, Esther (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)

Jewish labour and business in the dressmakers'strikes of tje 1930: A clash of cultures in a confined space - Tulchinsky, Gerald (Espace et culture, 1995)
Keywords: Grèves; Juifs; Vêtements

Le maintien de la langue d'origine chez des élèves maghrébins à Montréal et la réussite scolaire - Zouali, Ouafaa (Université Laval, 1995)
Keywords: Langue; Maghrébins; Étudiants

Le «boom» des immeubles d’appartements à Montréal de 1921-1951 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1994)
Number: 1
Keywords: Logement; Outremont; Westmount

Un royaume en exil: le judaïsme montréalais - Anctil, Pierre (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Juifs

Family, Paesani and Networks: Politics and Economy of Montreal Italians - Aramaki, Michiko (Université McGill, 1994)
Keywords: Italiens

Proposition d'un cadre de recherche opérationnelle pour l'étude de la ségrégation résidentielle ethnique dans la région métropolitaine de Montréal - Bérubé, Sylvain (Université de Montréal, 1994)

Safeguarding Mother Tamil in Multicultural Quebec: Sri Lankan Legends, Canadian Myths, and the Politics of Culture - Brunger, Fern (Université McGill, 1994)
Keywords: Sri Lankais

L'international, un devoir au quotidien depuis 1910 - Char, Antoine (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le)

Participation à la dynamique langagière et appartenance à la communauté linguistique: analyse du français parlé par des francophones et des anglophones de Montréal - Daveluy, Michelle (Université de Montréal, 1994)
Keywords: Langue

The Education of Italians in Montreal, 1895 to 1960 - Gadler, Yves Carmelo Luciano (Université McGill, 1994)
Keywords: Italiens

L'attitude des chinois de Montréal vis-à-vis des stratégies ethniques des banques - Hakimian, Edith (École des hautes études commerciales de Montréal, 1994)
Keywords: Banques; Chinois

Problèmes de communication interculturelle et ruptures des cadres chez des immigrants et immigrantes latino-américains à Montréal - Hudon, Nathalie (Université du Québec à Montréal, 1994)
Keywords: Latino-Américains

L'émergence d'une identité québécoise dans la dramaturgie anglo-montréalaise - Hulslander, Kenneth (Université du Québec à Montréal, 1994)
Keywords: Anglophones; Théâtre

Constructing Italian Ethnicity: A Comparative Study of Two Italian Language Newspapers in Australia and Canada, 1947-1957 - Iuliano, Susanna (Université McGill, 1994)
Keywords: Italiens

Le comportement électoral des minorités au Québec lors des élections de 1976 - Jedwab, Jack (Bulletin de l'association québécoise d'histoire politique, 1994)
issued: 1994-21-00
Keywords: Anglophones; Élections

Femmes immigrantes et sida: les Haïtiennes de Montréal - Landry, Gervaise Patricia (Université Laval, 1994)
Keywords: Femmes; Haïtiens

The Antiochan Orthodox Syrians of Montreal 1905-1980: an Historical Study of Cultural and Social Change Over Three Generations - Marino, Norman (Université Concordia, 1994)
Keywords: Syriens

Langage et ethnicité: communication interculturelle à Montréal, 1977-1991 - Moise, Lena C.; Bourhis, Richard Y. (Canadian Ethnic Studies / Études ethniques au Canada, 1994)
Number: 1
Keywords: Langue

Residential Patterns of New Immigrants and Linguistic Integration - Montgomery, Catherine; Renaud, Jean (The Canadian Geographer / Le Géographe canadien, 1994)
Number: 4
Keywords: Langue; Quartiers

Anomie et délinquance chez un groupe d'adolescents anglais de la région métropolitaine de Montréal - Rivest, Jean (Université du Québec à Montréal, 1994)
Keywords: Anglophones; Délinquance

Les Irlandais catholiques de Montréal: introduction historique et méthodologique - Slattery, Maureen (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Irlandais

Gender and Division of Labour in a Vietnamese-Canadian Buddhist Pagoda - Soucy, Alexander (Université Concordia, 1994)
Keywords: Femmes; Travail; Vietnamiens

Afro-Canadian Activism in the 1960s - Stamadianos, Peter (Université Concordia, 1994)
Afro-Canadian activism became increasingly militant in the 1960s. The rise in militancy in the Afro-American leadership of the 1960s was one factor contributing to the new era of black politics in Canada. Increased immigration from the West Indies also encouraged the proliferation of Afro-Canadian organizations dedicated to challenging racial discrimination. Afro-Canadian activism, however, developed in a substantially different manner than black politics in the United States. On the whole, most Afro-Canadian organizations and leaders were considerably less militant in their tactics and strategies than their counterparts in the United States. Internecine divisions over ancestral origin were also more pronounced in Canada where the black population was ethnically heterogeneous when compared to the Afro-American community.
Keywords: Africains; Noirs

Représentation de l'espace urbain et laïcisation de la pratique - Trépanier, Esther (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)

Catholicisme romain ou catholicisme culturel? À propos de la messe et d'autres pratiques rituelles chez les francophones du Grand Montréal - Turcotte, Paul-André (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)

Intra-Ethnic Differences of the Perceptions of Aged Italian Women in Receiving Care - Bonar, Rita Aguzzi (Université McGill, 1993)
Keywords: Femmes; Italiens

Enjeux et contraintes de la communication interculturelle au Québec: perceptions et réactions de la communauté juive montréalaise au théâtre de Michel Tremblay - Bonjour, Nathalie (Université du Québec à Montréal, 1993)
Keywords: Juifs; Théâtre; Tremblay; Michel

The traitor and the Jew: Anti-Semitism and Extremist Right-Wing Nationalism in Quebec from 1929 to 1939 - Delisle, Esther (Robert Davies Pub., 1993)
Translators: _:n31183
Keywords: Idéologies; Juifs; Nationalisme

«C'est l'eau-de-vie qui a commis ce meurtre». Alcool et criminalité amérindienne à Montréal sous le Régime français - Dickinson, John A. (Études canadiennes / Canadian Studies, 1993)
Number: 35
Keywords: Alcool; Autochtones; Criminalité

L'usage et la formation de l'énumération en discours spontané: analyse sociolinguistique du procédé énumératif chez les montréalais francophones - Dubois, Sylvie (Université Laval, 1993)
Keywords: Langue

Étude lexicale du livre des recettes et dépenses de l'Hôtel-Dieu de Montréal (1696 à 1726) - Francoeur, Sylvie (Université de Montréal, 1993)
Keywords: Communautés religieuses; Hospitalières de Saint-Joseph; Hôpitaux; Hôtel-Dieu; Linguistique

Les représentations sociales de la violence chez des adolescents et des adolescentes d'origines ethniques différentes de Montréal - Gobeil, André (Université Laval, 1993)
Keywords: Délinquance

Le sport chez les Canadiens-français de Montréal au XIXe siècle - Janson, Gilles (Université du Québec à Montréal, 1993)
Keywords: Baseball; Crosse; Football; Palestre nationale; Raquetteurs

Le monument inattendu, le Monument-National, 1893-1993 - Larrue, Jean-Marc (Hurtubise HMH, 1993)
Keywords: Société Saint-Jean-Baptiste; Théâtre; École nationale de théâtre du Canada

L'immigration française au Canada de 1945 à 1960 - Leblond, Francis (Université Laval, 1993)
Keywords: Français

Montréal. Une société multiculturelle - McNicoll, Claire (Belin, 1993)
Keywords: Mobilité résidentielle

L'identité ethnoculturelle chez des jeunes d'origine vietnamienne à Montréal - Méthot, Caroline (Université de Montréal, 1993)
Keywords: Vietnamiens

Étude comparative des voyelles nasales du français parisien et du français montréalais - Sanfaçon, Anne (Université de Montréal, 1993)
Keywords: Langue

Montréal, les Juifs et l'école - Siboni Corcos, Arlette (Université de Montréal, 1993)
Keywords: Juifs

101 du français, il en faut plus, pas moins - Société Saint-Jean-Bapiste de Montréal (L'Action nationale, 1993)
Number: 5
Keywords: Francophones

Les perceptions des groupes ethno-culturels face aux programmes communautaires du S.P.C.U.M. - Théagène, Jean-Manassé (Université de Montréal, 1993)
Keywords: Communauté urbaine

Ethnicité, culture et société globale: le discours de leaders d'origine haïtienne, italienne, juive et libanaise de la région de Montréal - Therrien, Marthe (Université du Québec à Montréal, 1993)
Keywords: Haïtiens; Italiens; Juifs; Libanais

Montreal Jewry in the Era of the de Solas - Tulchinsky, Gerald J. J. (Taking Root: The Origins of the Canadian Jewish Community, 1993)
Keywords: De Sola; Abraham; Juifs

Un shtetl dans la ville: la zone de résidence juive à Montréal avant 1945 - Anctil, Pierre (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Juifs

Rupture et continuité chez des familles québécoises francophones de Montréal: étude ethnologique des rapports entre parents âgés et enfants - Bédard, Jean-Luc (Université de Montréal, 1992)
Keywords: Famille

Montréal dans le réseau international des villes francophones - Breton, Roland J.-L. (Montréal: tableaux d'un espace en transformation, 1992)

Les relations interethniques et interraciales de parents haïtiens et de leurs enfants dans deux quartiers multiethniques de Montréal - Brodrique, Lise (Université du Québec à Montréal, 1992)
Keywords: Haïtiens; Quartiers

L’orientation linguistique des allophones à Montréal - Castonguay, Charles (Cahiers québécois de démographie, 1992)
issued: 1992-23-00
Keywords: Langue

Antisémitisme et nationalisme d'extrême-droite dans la province de Québec 1929-1939 - Delisle, Esther (Université Laval, 1992)
Keywords: Devoir (Le); Groulx; Lionel; Juifs; Nationalisme

Le traître et le juif: Lionel Groulx, Le Devoir, et le délire du nationalisme d'extrême droite dans la province de Québec: 1929-1939 - Delisle, Esther (L'Étincelle, 1992)
Keywords: Devoir (Le); Groulx; Lionel; Juifs; Nationalisme

Les associations vietnamiennes à Montréal - Dorais, Louis-Jacques (Canadian Ethnic Studies / Études ethniques au Canada, 1992)
Number: 1
Keywords: Vietnamiens

Un parler parisien - Faribault, Marthe (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)
Keywords: Français; Langue

Langue et identité chez les Québécois d’ascendance italienne - Fortier, Anne-Marie (Sociologie et sociétés, 1992)
issued: 1992-23-00
Keywords: Italiens; Langue

Origines, richesse et travail / Origins, Wealth and Work - Fyson, Donald; Young, Brian (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: Irlandais; McCord (famille)

La Grande Paix de Montréal de 1701: les voies de la diplomatie franco-amérindienne - Havard, Gilles (Recherches amérindiennes au Québec, 1992)
Keywords: Autochtones; Français; Grande Paix de Montréal

L’entrepreneurship ethnique à Montréal: première esquisse - Juteau, Danielle; Daviau-Guay, Jocelyne; Moallem, Minoo (Cahiers québécois de démographie, 1992)
issued: 1992-23-00

The Ideological and Intellectual Baggage of Three Fragments of Ukrainian Immigrants: a Contribution to the History of the Ukrainians in Quebec (1910-1960) - Kelebay, Yarema Gregory (Université Concordia, 1992)
Keywords: Idéologies; Ukrainiens

La communauté libanaise à Montréal: essai de géographie culturelle - Lami, Nathalie (Université du Québec à Montréal, 1992)
Keywords: Libanais

Les pierres qui parlent: deux cents ans d'enracinement de la communauté juive au Québec - Langlais, Jacques; Rome, David (Septentrion, 1992)
Keywords: Juifs

Les zones résidentielles des Indochinois à Montréal - Lavoie, Caroline (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Quartiers

The Italians of Quebec - Linteau, Paul-André (Boundaries of Identity: A Quebec Reader, 1992)
Keywords: Italiens

Rononshonni - le Bâtisseur. La collection McCord d'objets ethnographiques - McCaffrey, Moira T. (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: McCord; David Ross; Musée McCord; Musées

L’identité ethnique chez les jeunes Montréalais d’origine immigrée - Meintel, Deirdre (Sociologie et sociétés, 1992)
issued: 1992-23-00
Keywords: Chiliens; Grecs; Portugais; Salvadoriens

Montréal en Amérique du Nord - Mercer, John (Montréal: tableaux d'un espace en transformation, 1992)

Omer Héroux and La Vérité, 1904-1908: French-Canadian Nationalism and Catholicism in the Early Twentieth Century - Morrison, H. Jean (Université Concordia, 1992)
Keywords: Nationalisme; Écrivains

Beyond Physical Boundaries: The Symbolic Construction of Chinatown - Morrison, Val M. (Université Concordia, 1992)
Keywords: Chinois; Quartier chinois; Quartiers

Familles montréalaises du XIXe siècle: trois cultures, trois trajectoires - Olson, Sherry; Thornton, Patricia (Cahiers québécois de démographie, 1992)
issued: 1992-23-00
Keywords: Anglophones; Famille; Irlandais

Le chômage des jeunes de la communauté haïtienne de Montréal: les diplômés-es de l'UQAM - Pognon, Renel (Université du Québec à Montréal, 1992)
Keywords: Chômage; Haïtiens; Travail; Université du Québec à Montréal

Un an au Québec. La compétence linguistique et l’accès à un premier emploi - Renaud, Jean (Sociologie et sociétés, 1992)
issued: 1992-23-00
Keywords: Langue; Travail

Les représentations sociales des minorités ethniques dans la presse francophone montréalaise en 1989 - Rivière, Anne (Université du Québec à Montréal, 1992)

Institutional completeness, ethnic organizational style and the role of the state: the Jewish, Italian and Greek communities of Montreal - Rosenberg, Michael; Jedwab, Jack (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1992)
Number: 3
Keywords: Grecs; Italiens; Juifs

Immigration, acculturation et santé mentale: les Libanais à Montréal - Sayegh, Liliane (Université de Montréal, 1992)
Keywords: Libanais

Influence of the Jewish Dietary Laws (Kashruth) on the Food Habits and Nutritional Intakes of Observant Jews in Montreal - Shatenstein, Bryna (Université de Montréal, 1992)
Keywords: Alimentation; Juifs

Modes d'acculturation, stress acculturatif et race: le cas des jeunes étudiants haïtiens de la première et de la seconde générations de Montréal - Sylvestre, André (Université de Montréal, 1992)
Keywords: Haïtiens; Étudiants

Accessibility to Municipal Services for Ethnocultural Populations in Toronto and Montreal - Tate, Ellen (Université Laval, 1992)

Le comportement démographique des groupes linguistiques à Montréal - Termote, Marc (Cahiers québécois de démographie, 1992)
issued: 1992-23-00
Keywords: Anglophones; Francophones; Fécondité

Ukrainian Community Life in Montreal: Social Planning Implications - Tokar, Ann M. (Université McGill, 1992)
Keywords: Ukrainiens

Community Associations and their Relations with the State. The Case of the Arab Associative Network of Montréal - Aboud, Brian (Université du Québec à Montréal, 1991)
Keywords: Arabes

Struggling on Many Fronts: Gender, Work and Unionization - Aguiar, Luis (McMaster University, 1991)
Keywords: Textile; Vêtements

La fête du Santo Cristo à Montréal: histoire, idéologie et mentalité du peuple portugais - Araujo, Antonio (Université de Montréal, 1991)
Keywords: Portugais

La société canadienne-française et le théâtre lyrique à Montréal entre 1840 et 1913 - Barrière, Mireille (UMI Dissertation Services, 1991)
Keywords: Francophones; Théâtre

Nourriture et culture: étude des pratiques alimentaires des Chinois de Montréal - Bélanger, Danielle (Université de Montréal, 1991)
Keywords: Alimentation; Chinois

Modes d'acculturation et d'identité située: Le cas des immigrants haïtiens de Montréal - Clément, Richard; Sylvestre, André; Noels, Kimberly (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Number: 2
Keywords: Haïtiens

Intégration linguistique dans les écoles multiethniques de Montréal - Dubois, Jean-François (Université de Montréal, 1991)
Keywords: Langue

Les minorités ethniques et les décisions des juges du Tribunal de la jeunesse de Montréal - Faille, Michèle (Université de Montréal, 1991)
Keywords: Délinquance; Juges; Tribunaux

La construction sociale des relations interethniques et interraciales chez des jeunes vietnamiens et asiatiques du sud-est d'une école secondaire de Montréal - Filion, Gilbert (Université du Québec à Montréal, 1991)
Keywords: Vietnamiens

Smoke and Fire: The Chinese in Montreal - Kwok Bun, Chan (The Chinese University Press, 1991)
Keywords: Chinois

Jews & French Quebecers: Two Hundred Years of Shared History - Langlais, Jacques; Rome, David (Wilfrid Laurier University Press, 1991)
Translators: _:n6691
Keywords: Francophones; Juifs

Montréal en images: exotisme et triomphalisme (1855-1914) - Lessard, Michel (Cap-aux-Diamants, 1991)
issued: 1991-23-00
Keywords: Anglophones; Britanniques; Photographie

Les mécanismes privés d'accueil et d'assistance aux immigrants. Une étude de cas: la Société d'assistance aux immigrants, 1950-1957 - Lévesque, Edna (Université du Québec à Montréal, 1991)
Keywords: Société d'assistance aux immigrants

The Segregated City: Class Residential Patterns and the Development of Industrial Districts in Montreal 1861 and 1901 - Lewis, Robert D. (Journal of Urban History, 1991)
Number: 2
Keywords: Locataires; Logement; Mobilité résidentielle

Port du voile et profils d'appartenance chez des adolescentes musulmanes à Montréal - Machouf, Anousheh (Université de Montréal, 1991)
Keywords: Musulmans

La littérature montréalaise et les ghettos - Melançon, Benoît (Voix et Images, 1991)
Number: 3
Keywords: Quartiers; Écrivains

Historiography, Myth and Group Relations: Jewish and Non-Jewish Québécois on Jews and New France - Menkis, Richard (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Number: 2
Keywords: Histoire; Juifs

Église St. Patrick - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Irlandais; Patrimoine; Saint-Patrick (église)

Ethnic Strategies in the Urban Economy - Olson, Sherry (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Number: 2
Keywords: Travail

Sujets et identités multiples: analyse des histoires de vie d'un groupe d'immigrants italiens à Montréal - Peressini, Mauro (Université de Montréal, 1991)
Keywords: Italiens

On the Move: French-Canadian and Italian Migrants in the North Atlantic Economy, 1860-1914 - Ramirez, Bruno (McClelland and Stewart, 1991)
Keywords: Italiens; Travail

Par monts et par vaux. Migrants canadiens-français et italiens dans l’économie nord-atlantique, 1860-1914 - Ramirez, Bruno (Boréal, 1991)
Keywords: Italiens; Travail

Acculturation and Consumption Behaviour of Italian-Canadians in Montreal - Reedijk, Robert (Université Concordia, 1991)
Keywords: Italiens

Languages in Contact: Error Analysis of Italian Childrens' Compositions in a Multilingual Context - Samperi Mangan, Jacqueline (Université McGill, 1991)
Keywords: Enfants; Italiens; Langue

Jewish Supplementary Schooling in Montreal in the Latter Part of the Twentieth Century - Segal, Sima (Université McGill, 1991)
Keywords: Bureau des écoles protestantes; Juifs; Langue

Immigration et communautés ethno-culturelles - Taschereau, Sylvie (Guide d'histoire du Québec: du régime français à nos jours: bibliographie commentée, 1991)

The Attitudes of Students of Greek Origin in a French-Language Learning Situation in a Québec Secondary School - Waite, Richard (Université McGill, 1991)
Keywords: Grecs; Langue; Étudiants

A Coat of Many Colours. Two Centuries of Jewish Life in Canada - Abella, Irving (Lester and Orpen Dennys, 1990)
Keywords: Juifs

La tunique aux couleurs multiples. Deux siècles de présence juive au Canada - Abella, Irving (Musée canadien des Civilisations, 1990)
Keywords: Juifs

H.-M. Caiserman: Yiddish as a Passion - Anctil, Pierre (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs

La société canadienne-française et le théâtre lyrique à Montréal entre 1840 et 1913 - Barrière, Mireille (Université Laval, 1990)
Keywords: Francophones; Théâtre

Les Juifs Sépharades à Montréal: traces passagères et marqueurs spatiaux d'une minorité dans une métropole nord-américaine - Brière, Céline (Université d'Angers, 1990)
Keywords: Juifs; Métropole

La catéchèse à la Mission portugaise de Montréal - Bruno, Maria José (Université de Montréal, 1990)
Keywords: Missions; Portugais

Étude comparative des valeurs (rokeach) des groupes de jeunes d'origine québécoise, haïtienne et vietnamienne d'une école secondaire publique de Montréal - Chirca, Natalia (Université du Québec à Montréal, 1990)
Keywords: Haïtiens; Vietnamiens; Étudiants

Culture Change and the Redefinition of Ethnicity: the Case of Portuguese Youth in Montréal - Claudio, Fernanda (Université de Montréal, 1990)
Keywords: Portugais

Between Two Worlds: The Works of J.-I. Segal - Cooper Friedman, Shari (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Poésie; Segal; J. I.

Les associations vietnamiennes à Montréal et l'adaptation des réfugiés - Dorais, Louis-Jacques (Université Laval, 1990)
Keywords: Vietnamiens

The Journal of Yaacov Zipper 1925-1926 - Garfinkle, Ode; Butovsky, Mervin (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs

The Reconquest of Montreal. Language Policy and Social Change in a Bilingual City - Levine, Marc V. (Temple University Press, 1990)
Keywords: Anglophones; Francophones

Montreal of Yesterday: A Snapshot of Jewish Life in Montreal During the Era of Mass Immigration - M. Baker, Zachary (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Medres; Israel Jonah

The Ethnolinguistic Reality of Montreal Greeks - Maniakas, Theodoros (Université de Montréal, 1990)
Keywords: Grecs

Public Lives in Private: Ida Maze and the Montreal Yiddish Renaissance - Massey, Irving (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Poésie

Hometown and Family Ties: The Lebanese-Syrians of Montreal, 1905-1950 - Moser, Diane (Université McGill, 1990)
Keywords: Libanais; Syriens

Ethnicité et idéologie: le cas des italophones de Montréal - Oriolo, Stefano (Université Laval, 1990)
Keywords: Italiens

Itinéraires scolaires et socialisation ethnique: le cas de deux écoles judéo-québécoises - Prentice, Mark (Université Laval, 1990)
Keywords: Juifs

''A Letter from the Sabbath Queen'' Rabbi Yudel Rosenberg Addresses Montreal Jewry - Robinson, Ira (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Rosenberg; Yudel

The Kosher Meat War and the Jewish Community Council of Montreal, 1922-1925 - Robinson, Ira (Canadian Ethnic Studies / Études ethniques au Canada, 1990)
Number: 2
Keywords: Alimentation; Cohen; Hirsch; Juifs; Rosenberg; Yudel

An Everyday Miracle: Yiddish Culture in Montreal - Robinson, Ira; Anctil, Pierre; Butovsky, Mervin (Véhicule Press, 1990)
Keywords: Juifs